Reversible metamorphosis from Fe3O4 to FeO of epitaxial iron oxide films grown on the Fe-p(1 × 1)O surface. Issue 19 (19th March 2021) - Capra, M.; Lodesani, A.; Brambilla, A.; Finazzi, M.; Duò, L.; Ciccacci, F.; Picone, A.
Abstract : The reduction and oxidation of epitaxial Fe3 O4 films grown by reactive deposition on a Fe-p(1 × 1)O surface have been investigated by means of surface science techniques. Abstract : The reduction and oxidation of epitaxial Fe3 O4 films grown by reactive deposition on a Fe-p(1 × 1)O surface have been investigated by means of Auger electron spectroscopy (AES), low energy electron diffraction (LEED) and scanning tunneling microcopy (STM). The as-grown iron oxide samples display a square LEED pattern with a lattice constant compatible with a p(1 × 1) bulk terminated Fe3 O4 (001) surface. STM topographic images of Fe3 O4 are characterized by atomically flat terraces separated by highly oriented steps running along the (010) and (100) crystallographic directions of the substrate. Upon annealing at 800 K in an ultra-high vacuum, AES reveals that magnetite transforms to FeO. The sample exposes the (001) surface of the rock salt structure, with a lattice parameter close to that of bulk wüstite. The Fe3 O4 phase can be recovered by oxidation at 10 −6 mbar of molecular oxygen.